2017
DOI: 10.1590/0104-1428.02016
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein-based films incorporated with oregano essential oil

Abstract: This study aimed to prepare whey protein-based films incorporated with oregano essential oil at different concentrations, and evaluate their properties and antimicrobial activity. Films were more flexible with increasing the concentration of oregano oil and water vapor permeability was higher in the films with oregano oil. Increasing the concentration of essential oil decreased the water solubility. The solubility of control film and film with 1.5% oregano oil was 20.2 and 14.0%, respectively. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…A study reported that whey protein-based films incorporated with oregano and garlic essential oil resulted in larger inhibitory zones on Gram-negative (Escherichia coli and Salmonella Enteritidis) and Gram-positive bacteria (Staphylococcus aureus, Lactobacillus plantarum, and Listeria monocytogenes) [38], while another study of whey protein-based films incorporated with oregano essential oil showed antimicrobial activity against fungus species (Penicillium commune) [39]. The inhibition toward the microorganism was prompted by thymol and carvacrol compounds that are mainly present in essential oil.…”
Section: Whey Protein-based Film As Active Packagingmentioning
confidence: 99%
“…A study reported that whey protein-based films incorporated with oregano and garlic essential oil resulted in larger inhibitory zones on Gram-negative (Escherichia coli and Salmonella Enteritidis) and Gram-positive bacteria (Staphylococcus aureus, Lactobacillus plantarum, and Listeria monocytogenes) [38], while another study of whey protein-based films incorporated with oregano essential oil showed antimicrobial activity against fungus species (Penicillium commune) [39]. The inhibition toward the microorganism was prompted by thymol and carvacrol compounds that are mainly present in essential oil.…”
Section: Whey Protein-based Film As Active Packagingmentioning
confidence: 99%
“…Por outro lado, alguns autores relatam que o efeito plastificante de óleos essenciais depende do tipo de óleo e polímero utilizado na formulação do filme e da interação entre esses compostos [24] . Em filmes de proteína do soro de leite (WPC), por exemplo, o filme controle teve uma RT menor que os filmes adicionados de OEO nas proporções de 0,5, 1 e 1,5% [8] , sugerindo que em menores concentrações, o OEO não apresenta um efeito plastificante tão pronunciado.…”
Section: Propriedades Mecânicasunclassified
“…Valores similares de PVA foram obtidos em outros estudos sobre produção de filmes a base de proteínas [12,13,25] . Avaliando o efeito da adição de OEO, comparando-se com a amostra G20, houve elevação significativa nos valores de PVA e resultado semelhante foi descrito por Oliveira et al (2017) [8] em filmes de WPC adicionados de OEO. Resultado diferente foi reportado por Carpiné et al (2016) [25] , que observaou que a adição de óleo de coco e extrato de Yuccaschidigera diminuiu em aproximadamente 35,4% a PVA dos filmes em relação ao filme controle.…”
Section: Tabelaunclassified
See 1 more Smart Citation
“…38 The antimicrobial activity of whey protein-based films was evaluated by incorporation of oregano essential oil and it was observed that the films containing 1.5% oregano oil had higher antimicrobial activity and the zone of inhibition ranged from 0 to 1.7 cm. 61 Bahram et al, 62 observed the antimicrobial effects for whey protein concentrate (WPC) based edible film prepared by incorporating cinnamon essential oil (CEO) at a level of 0.8 and 1.5% v/v. Films containing CEO demonstrated appreciable antibacterial activity against both gram-positive and gram-negative strains, and exhibited good inhibitory action on the fungi.…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%